Métodos e atributos fisico-químicos para previsão da degenerescência da polpa em maçãs armazenadas em atmosfera controlada - Neuwald, Daniel Alexandre (2008)
The objectives of this work was to estimate the potential of flesh browning development in Gala , Royal Gala , Fuji e Braeburn apples after controlled atmosphere storage (CA). This study was realized through correlation of predictive methods and fruit quality and ripening parameters with the flesh browning occurrence after CA storage. Experiments were carried out with fruits from different orchards and years. In 2004, a first experiment was carried out with Fuji apples from three orchards. In 2005, Gala , Royal Gala , Fuji and Braeburn apples were evaluated from 11 orchards using two picking dates. Theses experiments were carried out at the Núcleo de Pesquisa em Pós-colheita of Federal University of Santa Maria, Santa Maria, Brazil with fruits from Vacaria, RS, Brazil. In 2006 to 2007 experiments were carried out in Germany using Braeburn apples from seven orchards. These methods the disorder occurrence after six months CA storage was correlated with the predictive methods, and with quality and ripening parameters. The predictive methods evaluated were: Mg infiltration, maturity acceleration with ethephon, and stress induction with high CO2. It was also evaluated the capacity of chlorophyll-fluorescence to detect possible stress occurrence on fruits exposed to high CO2 concentrations. Results show that in Fuji fruit juice percentage were able to predict flesh browning, but only in high CO2 (2.0 kPa) CA condition, while TSS level has been able to predict the occurrence of this disorder in fruits stored in low CO2 (<0.5 kPa). The chlorophyll fluorescence was capable of detect stress in fruits caused by exposure to high CO2 at harvest, and with this method it could be predicted the occurrence of physiological disorders in early harvested and with delay CA storage. By nutritional analysis of fruits, the level of K show high correlation with the occurrence of flesh browning after the CA storage of Braeburn apple. Some predictive methods and quality parameters evaluated at harvest were able to predict flesh browning occurrence in apple stored, in certain storage conditions, but in other storage conditions there wasn t significant correlation between flesh browning and this predictive methods and quality parameters. These predictive methods and quality parameters do not show high correlation with flesh browning in all situations.